Multiple borders of Nagorno-Karabakh - Vladimir A. Kolosov; Maria V. Zotova (Geography, Environment, Sustainability)
Though the agreement on ceasefire between Armenian and Azerbaijani troops in Nagorno-Karabakh was concluded more than 25 years ago, there is no progress in the negotiations between the sides. The conflict is intrinsically related to the partition of territory between the areas de facto controlled by the non-recognized Republic of NagornoKarabakh, boundaries of which do not match the administrative borders of Nagorno-Karabakh Autonomous Region in the Soviet period, and Azerbaijan. This paper considers the geopolitical situation of Nagorno-Karabakh through the lenses of its cross-border interactions and bordering. This notion widely used in contemporary border studies means not only border delimitation and management, but also the constant process of change in their functions, regime, and social importance. Such change can result, for instance, from the transformation of political strategies, shifts on the international arena and bilateral relations, currency exchange rates and global market prices, as well as in the course of the everyday practice and interactions. The authors analyzed first the existing pattern of borders in the context of security. Then they characterized de-bordering and interactions between Nagorno-Karabakh and its patron state, Armenia, describing the adaptation of the Karabakhi population and economy to the lack of international recognition. The demarcation line with Azerbaijan remains one of the rare cases of a completely closed border. One of the main and potentially long-term obstacles in finding a solution is the cultivation of the «image of the enemy» on both sides of this border.